Inside Cover: Anodic Chlorination of Selenophene‐Containing Polymers: Reaction Efficiency and Selective Reaction of Single Segment in Rod−Rod Diblockcopolymer (ChemElectroChem 8/2017). Issue 8 (28th June 2017) - Shida, Naoki; Okazaki, Daichi; Kurioka, Tomoyuki; Nishiyama, Hiroki; Seferos, Dwight S.; Tomita, Ikuyoshi; Inagi, Shinsuke
Abstract : The Inside Cover picture describes the unprecedented segment‐selective electrochemical transformation of a rod–rod diblock copolymer, in which the reaction proceed at a single segment of the copolymer, owing to the difference in oxidation potentials and side‐chain structures of the segments. More details can be found in the Communication by N. Shida et al. onpage 1824 in Issue 8, 2017 (DOI:10.1002/celc.201700205 ).